Effect of Powtoon Media and Problem Based Learning Model on Accounting Student Learning Outcomes - Yhonara, Merlyana Agnes; Astuti, Elly; Styaningrum, Farida (Jurnal Inovasi Teknologi Pendidikan, 2022)
This study aims to determine whether there is a difference in the effect of the Problem Based Learning learning model and Powtoon learning media and the interaction of the influence between the learning model and learning media on student learning outcomes. This research was conducted on students of SMK Accounting with a total of 131 students. The research was conducted using a quantitative method of quasi-experimental research with data collection techniques using multiple-choice learning outcomes tests that have been tested through a two-way ANOVA test and followed by the Pos hoc Tukey test. Data processing in this study used SPSS 16. The results showed that: (1) There was a significant difference in the effect of the Problem Based Learning learning model on student learning outcomes. (2) There is a significant difference in the effect of Powtoon learning media on student learning outcomes. (3) There is a significant interaction effect between the Problem Based Learning learning model and Powtoon learning media on student learning outcomes.